Pengaruh Profitabilitas, Laverage, dan Growth Terhadap Nilai Perusahaan pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia (BEI) - suwandi suwandi (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2014)
Profitability, Laverage, and Growth was strongly related to Peruusahaan value. Any company that is able to generate good profitability, the development will also look good. Laverage always required the company to run the company, these variables describe sebeapa large companies have an obligation to be paid. Growth can describe the company pmengalami increase or decrease. Types of research are used by these researchers is the type of correlational research and quantitative methods. Collecting data using the data of secondary data. The results show that profitability, Laverage, and Growth simultaneously significant effect on Firm Value, with a significant level of 0.043 under the significant level of 0.05. While partially variable Profitability, Laverage, and Growth does not have a significant effect due to a significant level above 0.05.